Efektivitas Komunikasi Dakwah Di Pesantren MQ dalam Merubah Akhlak Santri - Agus Sudiansyah (Communicatus: Jurnal Ilmu komunikasi, 2017)
Indonesia has different types of educational institutions including a state owned institution and a private one. However, recently, several types of educational institutions in Indonesia have some attention from the society in terms of the development of behavioral character of the youth that tend to be degrading. Effective communication of dakwah(preaching) at Pesantren MQ Tebuireng (MQ Tebuireng Islamic Boarding School) as well as akhlak(behavior) education is believed to be able to improve the behavior or so called akhlak of the Indonesian youth to be better. It can be seen from this study, a study at Pesantren MQ Tebuireng aimed at finding the influence and correlation between the effectivity of communication of dakwah and akhlak education towards students. This study is a Quantitative study. The data in this study are obtained through survey using a proportional stratification sample tehnique towards 172 students at Pesantren MQ Tebuireng. The study shows that there is a simultaneous influence between an effective communication of dakwah and akhlak education towards students where Fcount of 18.009 > Ftable  of 3.05. However, there is also a correlation with r value of .749. According to Priyato, the r value of .60 - .799 shows a strong correlation, i.e. between the effectivity of communication of dakwah and akhlak education towards students. Indonesia memilki bebearapa lembaga pendidikan, yakni lembaga pendidikan milik pemerintah dan lembaga milik per orangan, sedangkan sekarang beberapa  lembaga pendidikan di Indonesia mendapat sorotan dari masyarakat mengenai pengembangan karakter tingkah laku generasinya yang mulai menurun. Komunikasi dakwah yang efektif di Pesantren MQ Tebuireung dan pembinaan akhlak  diyakini dapat meningkatkan tingkah laku atau akhlak generasi di Indonesia menjadi lebih baik. Terbukti hasil penelitian di Pesantren MQ Tebuireung dengan tujuan ingin mengetahui pengaruh dan hubungan  efektivitas komunikasi dakwah dan pembinaan akhlak terhadap akhlak santri. Penelitian ini merupakan penelitian Kuantitatif. Data dikumpulkan melaui survei dengan teknik sampel stratifikasi proporsional terhadap santri di Pesantren MQ Tebuirung berjumlah 172 santri. Hasil penelitian menunjukan terdapat pengaruh secara simultan dengan F Hitung 18,009> F Tabel 3,05, komunikasi dakwah yang efektif dan pembinaan akhlak terhadap akhlak santri, dan terdapat hubungan atau korelasi dengan r sederhana dengan nilai 0,749, menurut Priyato nilai 0,60-0,799 sangat kuat hubungannya dari efektivitas komunikasi dakwah dan pembinaan akhlak terhadap akhlak santri.